Effectiveness of using the Nintendo Wii® video game as a therapeutic resource in the rehabilitation of children with cerebral palsy: integrative review - Borges, João Carlos de Sousa (2023)
Cerebral Palsy (CP) is a disorder in posture and movements resulting from a lesion in the central nervous system, non-progressive and non-evolutionary that can be acquired before the first two years of life. It has several etiologies as causes, these factors hinder the performance of activity, also affects balance and makes postural control difficult. Virtual reality (VR) has been an excellent therapeutic resource for children with CP, with the Nintendo Wii being one of the concepts of VR, which allows motor interaction between the player and the machine. To analyze the effectiveness of using the Nintendo Wii® video game as a therapeutic resource in the rehabilitation of children with cerebral palsy. An integrative review was carried out that analyzed the effectiveness of using the Nintendo Wii in the treatment of children with cerebral palsy. Searches were performed in the following databases PubMed, BVS/MEDLINE and ScienceDirect. The search strategy included a combination of the following descriptors: “cerebral palsy” and “nintendo wii” and “virtual reality”. Six articles were identified that met the inclusion criteria. Since the studies should evaluate at least one of the following outcomes of interest: balance, gross motor function and manual function. It is concluded, therefore, that the use of the Nintendo Wii is effective for increasing balance, gross and manual function in children with CP, but studies with a larger population are needed to present NW as a complementary rehabilitation therapy.